2005
DOI: 10.1123/mcj.9.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Reaching in Children with Spastic Hemiparetic Cerebral Palsy under Different Task Demands

Abstract: Coordination of reaching with the impaired and non-impaired arm in 10 children with spastic hemiparetic cerebral palsy (SHCP) was examined in a stationary ball and moving ball context. Kinematic data on trunk, arm, and wrist movements, and coordination patterns between joint angles of elbow, shoulder, and trunk, were analyzed to determine how reaching was influenced by impairment and object motion. Results showed longer deceleration time and movement time and greater trunk contribution following decreased elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 18 publications
6
41
0
1
Order By: Relevance
“…In the tracing task, there was a significant difference between the arms for path length, with the non-affected arm tracing a path over a fifth shorter than the affected arm. Our findings are consistent with previous reports within the literature of reduced performance in the affected arm of children with unilateral cerebral palsy 2,3 .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In the tracing task, there was a significant difference between the arms for path length, with the non-affected arm tracing a path over a fifth shorter than the affected arm. Our findings are consistent with previous reports within the literature of reduced performance in the affected arm of children with unilateral cerebral palsy 2,3 .…”
Section: Resultssupporting
confidence: 83%
“…We postulated that the Culmer et al 25 tasks could be adapted for children with CP and produce similar kinematic measures as previous laboratory based studies 2,3,20 . We This feasibility study was designed to: (i) test the capability of CPKAT to capture high quality kinematic data in a non-laboratory setting; (ii) compare the findings to previous kinematic evaluations in the CP population; (iii) investigate whether CPKAT could detect differences between the impaired and unimpaired arms of children with unilateral CP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in the reach movements of the nonimpaired arm compared to the impaired arm are characterized by some of the typical movement limitations imposed by SHCP. For example, it is often reported that there is less elbow excursion accompanied with more trunk involvement, as well as lower velocity movements when using the impaired arm compared to the non-impaired arm [2].…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of upper limb movements, characterized by increased duration, reduced peak velocity, increased variability and less straight hand trajectories [2][3][4] , is present in up to 80% of children with cerebral palsy. Upper limb difficulties cause activity limitation for children with cerebral palsy, activity being defined as the execution of a task or action by an individual 6 .…”
Section: Introductionmentioning
confidence: 99%